Effect of double-filtration plasmapheresis for antibody-mediated rejection on hemostasis parameters and thrombin generation. Issue 166 (June 2018) - Marlu, R.; Malvezzi, P.; Seyve, L.; Jouve, T.; Maurizi, J.; Defendi, F.; Carron, P.L.; Christophe, M.; Le Gouellec, A.; Polack, B.; Rostaing, L.
Abstract: Introduction: Donor-specific alloantibodies (DSAs) cause kidney-allograft loss in chronic antibody-mediated rejection (CAMR). Treatment relies on blocking antibody-producing cells and removing DSAs by apheresis: e.g., double-filtration plasmapheresis (DFPP). Materials and methods: To determine the impact of DFPP (6 or 8 sessions/patient) on clotting factors and natural anticoagulants, and on thrombin generation, we performed a prospective and observational study in five CAMR kidney-transplant patients who received DFPP plus rituximab therapy. Thrombin generation was performed in poor platelet plasma (PPP) with 5 pM tissue factor without and with 2 nM recombinant human thrombomodulin. Results: After the first DFPP session, median levels of high molecular-weight proteins (fibrinogen, FV, FVIII, FXI, FXIII, von Willebrand factors and α2-MG) decreased significantly to <50% of baseline values, whereas levels of low molecular-weight factors (<100 kDa) were not significantly modified, except for protein S and TFPI. Of note, binding-protein (BP) S, i.e., C4BP, was significantly decreased. Over the course of successive DFPP sessions, both high and lower molecular-weight proteins (<100 kDa) with longer half-lives (>2 days, prothrombin and factor XII) were significantly decreased. DFPP also highly affected thrombin generation in the absence of thrombomodulin but not significantly in the presence of thrombomodulin. After the first DFPP session, mean endogenous thrombin potential (ETP) and peak thrombin (PH) significantly decreased when the thrombin generation assay was performed without thrombomodulin (respectively, 1084 nM·min for ETP and 210 nM for PH after the first DFPP session compared to 1616 nM·min and 264 nM at baseline). In the presence of thrombomodulin, there was only a slight decrease in ETP and PH (respectively 748 nM·min, and 172 nM after the first DFPP session compared to 822 nM·min and 179 nM at baseline). After the last session, median ETP and PH decreased respectively to 646 nM·min and 143 nM without thrombomodulin, and, to 490 nM·min and 117 nM with thrombomodulin. Conclusions: DFPP significantly removed high molecular-weight proteins from the haemostatic system and profoundly decreased levels of protein S and TFPI. Overall thrombin-generation balance was only moderately affected in the presence of thrombomodulin. Nevertheless, high depletion of fibrinogen, FXIII and Von Willebrand Factor may expose patients to an increased risk of bleeding. Highlights: Double-filtration plasmapheresis (DFPP) is used to treat chronic antibody-mediated rejection in kidney-transplant patients. We assessed the effect of DFPP on the clearance of clotting factors and natural anticoagulants. The clearance of hemostatic proteins was highly dependent on their molecular weights, except for protein S and TFPI. DFPP induced high depletion of FXIII, fibrinogen and VWF. DFPP induced only a slight decrease in thrombin generation in the presence of thrombomodulin.